2020
DOI: 10.36103/ijas.v51i6.1202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Substitution Spirulina Instead of Soybean Meal in Common Carp Cyprinus Carpio L. Diet on Some Blood Picture and Some Biochemical Criteria

Abstract: This study conducted to find the effect of partial replacement of soybean meal by Spirulina Arthospira platensis on some blood picture and biochemical criteria in  common carp Cyprinus carpio. Fish were fed on five experimental diets contained spirulina with ratio 1.45%, 2.90%, 3.54% and 6.10% of the total diet as well as control ( without spirulina) for 56 days . Results of the statistical analysis showed a significant decrease (p≤ 0.05) in the concentration of hemoglobin in treated fish fed on spirulina diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…The greatest improvement in growth performance was seen in the first weeks after adding gum arabic at varying concentrations to the ration, as shown by our results showing a significant superiority of the T4 treatment (6.5 gm of gum arabic / kg of feed) in the rate of weight gain. Our results are in line with the results of [30][31][32], who found that broiler chickens showed a higher growth rate compared to an improvement in the feed conversion factor.…”
Section: Feed Conversionsupporting
confidence: 93%
See 2 more Smart Citations
“…The greatest improvement in growth performance was seen in the first weeks after adding gum arabic at varying concentrations to the ration, as shown by our results showing a significant superiority of the T4 treatment (6.5 gm of gum arabic / kg of feed) in the rate of weight gain. Our results are in line with the results of [30][31][32], who found that broiler chickens showed a higher growth rate compared to an improvement in the feed conversion factor.…”
Section: Feed Conversionsupporting
confidence: 93%
“…Some productive characteristics of broiler chickens were demonstrated by the use of 150 unsexed Ross 308 broiler chicks randomly assigned to 5 treatments, with 3 replications for each treatment and each replicate comprising 10 chicks, "distributed within pens with dimensions of 1 x 1 m 2 and added gum arabic to ration, and beginning on the first day of the experiment, the treatments were as follows: T1: control treatment without addition T2: add 2.5 gm of gum arabic / kg feed T3: add 4.5 gm of gum arabic / kg feed T4: add 6.5 gm of gum arabic / kg feed T5: add 8.5 gm of gum arabic / kg feed From day one to the third week of life, the chicks were fed starting food (22.03% protein and 2914.25 kilocalories/kg of feed); after that, they were switched to growth diet (19.87% protein and 3014.95 kilocalories/kg of feed). Fodder) and water were fed ad libitum (at will) and the diet followed was that shown in Table (1) up until the conclusion of the fifth week. We calculated the feed conversion coefficient, total feed consumed, weight increase, and live body weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously recorded that biochemical markers of the liver (ALT and AST) in Oreochromis niloticus are influenced by this microalgae [34]. It is not doubt that the roles of spirulina acting as an antioxidant which prevent the formation of ion radicals [35].…”
Section: Discussionmentioning
confidence: 72%
“…There are many types and high prices, and the same type is not constantly available in the market, in addition to containing compounds that are difficult to detect in local laboratories, and the inability to verify their quality, content, and health safety, which have damage to the health of birds [3]. Recent studies directed to finding alternatives through the use of natural food additives [4][5][6][7] by replacing protein concentrates and substituting essential amino acids in order to obtain economical diets with a low protein level that are not stressful for the bird and maintain the general health of the bird [8]. Proteins are among the basic compounds needed by the bird, and they have various functions within the bodies of living organisms, including structural and productive functions, stimulating metabolic reactions, and are considered a source of energy [9].…”
Section: Introductionmentioning
confidence: 99%